An Analysis of Themes in The Casher Short Story by John Collier - Laksmiari, I Gusti Ayu; Mulyana, Novita; Ediwan, I Nyoman Tri; Utami, Gek Wulan Novi (VISA: Journal of Vision and Ideas, 2024)
The study examines the theme of “The Chaser” a short story by John Collier. "The Chaser," is known for his complex themes, the contrariety between love and obsession, explores the moral dilemmas that arise when persons attempt to control and manipulate the emotions of others, etc. This study aims to find out the theme of "The Chaser" by John Collier to gain a deeper understanding of the story, because themes provide layers of meaning to a story. The data of this study was taken from the short story entitled “The Chaser” by John Collier. This short story was chosen as the data of this study because this story is easy to understand and has some themes, it provides a basis for deeper analysis. The data was collected through library research and the to collect the data, the researcher applied some steps. The first step is reading the whole story of “The Chaser”, the second step is understanding the story, and the last step is identifying the themes of the story. The data was analyzed using qualitative method. The result shows that there are four major themes in “The Chaser” short story, they are they are love, obsession and desire, changes and loss of individuality, and irony. The analysis dives into how the protagonist, Alan Austen, attempts to earn Diana's affection by unconventional tactics, delving into the deep issues of love and the consequences of obsessive desire. The story depicts the ironic twist in Alan's desire for love, highlighting the risks of loss of individuality associated with such pursuits.